More efficient North Atlantic carbon pump during the Last Glacial Maximum - J. Yu (Nature Portfolio, 2019)
Atmospheric CO2 is governed by CO2 gains (e.g., via Southern Ocean outgassing) and losses (e.g., via North Atlantic absorption). Using a novel method to estimate air–sea CO2 exchange signals, the authors show that North Atlantic CO2 absorption became more efficient and contributed to lowering atmospheric CO2 during ice ages.